ANALISIS PENERAPAN ASAS TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DI KELURAHAN PUCANG KECAMATAN SIDOARJO KABUPATEN SIDOARJO - Lailatur Rohmah; Dian Fahriani (Bajang Institute, 2022)
This study means to decide how the use of cashless transaction in monetary administration in Pucang Village, Sidoarjo District, Sidoarjo Regency. Specialists as a scientific device in research. Meetings, perceptions, and reports are utilized as a device to acquire information during research in the field. This examination utilizes clear subjective techniques, in particular the information gathered as words, pictures, and tables to give an outline of the application as non-cash exchanges in monetary administration in Pucang Village as Sidoarjo Regent Regulation Number 9 of 2019 and Sidoarjo Regent Regulation Number 7 In 2018. Cashless transaction in Pucang Village are completed utilizing an online electronic application called SIKSDA, and should be possible in 2 (two) ways, to be specific SPP GU and SPP LS. Monetary administration in Pucang Village goes through 2 (two) stages, in particular arranging, execution and organization